LEARNING WHICH ORIENTED ON LOCAL WISDOM TO GROW A POSITIVE APPRECIATION OF BATIK JUMPUTAN (IKAT CELUP METHOD) - Atmojo, S. E. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This study aims to identify the elements of science in the process of batik jumputan as the local culture. By knowing the existence of the elements of science in batik jumputan, expected to foster a positive appreciation of batik jumputan as a local cultural heritage. Based on the results of questionnaire analysis, we know that the growing appreciation before and after learning of the profession WHO batik makers are at high criterion (0.70 g). The results of the observation science process skills while making batik we can conclude it to the average score of science process skills (60% KPS 80%) are located in the high category.